2021
DOI: 10.2166/wp.2021.120
|View full text |Cite
|
Sign up to set email alerts
|

Midterm impacts of a water drought experience: evaluation of consumption changes in São Paulo, Brazil

Abstract: From late 2013 until the beginning of 2015, the metropolitan region of São Paulo, Brazil, experienced a severe water shortage. During that period, economic incentives were implemented by the regional water provider in a successful attempt to reduce water consumption. We aimed to investigate whether such incentives, as well as the experience of a scarcity period itself, had a persistent impact on consumer behaviour after the water crisis was over. This study was conducted by means of a hierarchical linear model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The literature also shows that the water availability context influences people to incorporate water-saving behavior (Wang & Dong, 2017;Stone & Johnson, 2022;Sousa et al, 2022). This happens because people feel the seriousness of the situation and generally understand that they are part of the problem as well as part of the solution (Gilbertson et al, 2011), and that is why, in our framework, the context influences psychological factors.…”
Section: Proposed Frameworkmentioning
confidence: 92%
See 4 more Smart Citations
“…The literature also shows that the water availability context influences people to incorporate water-saving behavior (Wang & Dong, 2017;Stone & Johnson, 2022;Sousa et al, 2022). This happens because people feel the seriousness of the situation and generally understand that they are part of the problem as well as part of the solution (Gilbertson et al, 2011), and that is why, in our framework, the context influences psychological factors.…”
Section: Proposed Frameworkmentioning
confidence: 92%
“…Nevertheless, in more recent years, studies have shown that these factors alone are inconsistent in predicting environmental behaviors; thus, they have been used mainly to segment information, such as creating clusters (i.e., gathering households/inhabitants with similar characteristics) and investigating similar consumption patterns within such clusters (Wolters, 2014;Ibrahim et al, 2018;Villar-Navascués & Pérez-Morales, 2018;Rodonic, 2019;Sousa & Fouto, 2019;Ibrahim et al, 2021;Ito et al, 2021;Kumar, Sharma, Tabhani, & Otaki, 2021;Sousa, Teixeira, & Fouto, 2022). In the present literature review, socioeconomic and demographic factors were the main topic in only 8 of the 55 articles; however, variables associated with these factors were present in more than half of the studies read for this review (33 out of 55).…”
Section: Socioeconomic and Demographic Factorsmentioning
confidence: 99%
See 3 more Smart Citations